Growing and Handling of Bacterial Cultures - Mishra, Madhusmita (IntechOpen, 2019)
Growing and Handling of Bacterial Cultures is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Life Sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the field. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on Growing and Handling of Bacterial Cultures, and open new possible research paths for further novel developments.